Adjustable computerized stereotaxic brain atlas for transmission and emission tomography. - Bohm, C; Greitz, T; Kingsley, D; Berggren, B M; Olsson, L (American Journal of Neuroradiology, 1983)
A computerized brain atlas adjustable to the patient's anatomy would serve serveral purposes. It could be used in stereotaxic surgery. Even more important would be its use in medical imaging to identify various brain structures, such as the basal ganglia and their nuclei, as well as individual cortical gyri. This atlas could be used for additional mapping of nonvisible structures in images obtained with methods having a high spatial resolution, such as computed tomography and nuclear magnetic resonance. Anatomic information obtained in this way might then be transferred to images of low resolution, such as those obtained in positron emission tomography or single-photon emission computed tomography, in order to select anatomically correct regions of interest. The methods used in the construction of such an atlas are briefly described. An attempt to implement such an atlas based on digitized photographs of brain slices is described.